CUIDADOS ALTERNATIVOS PARA CRIANÇAS GUARANI E KAIOWÁ AFASTADAS DA FAMÍLIA, A PARTIR DO PLURALISMO JURÍDICO - KATY BRAUN DO PRADO (2024)
The aim of this dissertation is to contribute to the development of legal solutions for the provision of adequate alternative care for Guarani and Kaiowá children, based on legal pluralism. Mato Grosso do Sul has the third-largest indigenous population in the country, with a predominance of two genetically related ethnic groups: Guarani Kaiowá and Guarani Nhandéva. Among the state's indigenous peoples, Guarani and Kaiowá children and adolescents are the most socially vulnerable and disproportionately make up the number of children in foster care, based on the state's population. This is an inductive method study, with a qualitative-quantitative approach as well as exploratory and descriptive types, using bibliographic survey procedures and documentary sources related to the subject. In addition, data from the National Adoption and Foster Care System, of the Brazilian National Council of Justice, up to the date of January 20, 2024, with registration of 732 children in family and institutional foster care services in Mato Grosso do Sul. 68 of them indigenous children, 60 of them Guarani and/or Kaiowá. Thus, the problem of this research raises the question of the causes of such a significant number of removals from their families and communities and whether this is related to the national history of indigenous policies, as well as whether the fundamental rights of these indigenous children and adolescents have been ensured by the rights guarantee system. It was found that the confinement of indigenous peoples in reserves has led to the break-up of families and the dismantling of their social organizations, which caused the weakening of traditional leaders, exposure to diseases, cases of malnutrition, distancing from ancestral religious practices, alcohol and drug abuse, a wave of suicides and the consequent distancing of children from their parents and the community, in situations of social or personal risk. From the perspective of legal pluralism and the establishment of the practice of dialogue by the Judiciary between the norms of the global, regional and domestic systems for the protection of children, adolescents and, in general, indigenous peoples, legal solutions were proposed, in accordance with the Brazilian constitutional bloc, aiming to reduce violations of the rights of Guarani and Kaiowá children deprived of parental care. With the guidelines recommended in this work, we hope to contribute to the enjoyment of the right to family and community life for Guarani and Kaiowá children, one of the means of guaranteeing a dignified existence not only for these ethnic groups, but for all of Brazil's indigenous peoples.